Studi Kesesuaian Perairan Pulau Pisang Bagian Timur Untuk Perencanaan Wisata Bahari Selancar Air, Olahraga Air Banana Boat dan Jet Ski, Kabupaten Lampung Barat, Provinsi Lampung - Pradana, Andika Nugraha; Hariyadi, Hariyadi; Subardjo, Petrus (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Banana Island is one destination that superior Lampung attractions and is a tourist attraction in West Lampung regency which has considerable potential as one of the coastal resorts.This study aims to identify and assess physical potential of Cape Coast Faithful as marine tourism area.This study aims to identify and assess the potential physical Banana Island as a marine tourism area.This study was conducted in July-August 2011, this is because the month is a transition season, which allegedly started the season many tourists flock to Banana Island for a tour. The method used in this research is descriptive exploratory method.The analysis used in this study is an analysis of the suitability of travel, ie by comparing the characteristics and quality of the waters of the requirements for the use of waters of certain tourist activities. Results of the study showed that the physical conditions potentially Banana Island waters as marine tourism area, with several activities, namely water surfing (surfing), and water sports (Water Sports) ie banana boat and jet ski. Based on the value IKW for surfing activities (Surfing) in the category of S1-class (very appropriate) with IKW value by 86%, while for the water sports activities (Water Sport) ie banana boat and jet ski into the category of S1-class (very appropriate ) with IKW value of 81%.